The impact of the COVID-19 pandemic on job satisfaction among professionally active nurses in five European countries - Makowicz, Dawid; Lisowicz, Katarzyna; Bryniarski, Krzysztof; Dziubaszewska, Renata; Makowicz, Natalia; Dobrowolska, Beata (Frontiers in Public Health, 2022)
The COVID-19 pandemic has negatively affected the work of many medical professionals, including the group of nurses. This study aimed at assessing the impact of the COVID-19 pandemic on job satisfaction of nursing staff in five European countries. The study was conducted using the Job Satisfaction Scale (SSP) and original questions on the job satisfaction. The cross-sectional online study was conducted with a sample of 1012 professionally active nurses working in Poland, Germany, Italy, Great Britain and Sweden, who assessed their job satisfaction before (retrospectively) and during the pandemic. The results showed a significant decrease in job satisfaction due to the need to perform it during the pandemic caused by the SARS-CoV-2 virus. In 8 out of 10 examined parameters of job satisfaction, a statistically significant decrease in job satisfaction was observed at the level of p<0.05. Among the examined factors influencing job satisfaction, the highest decrease was recorded based on the assessment of working conditions (1,480). A high level of satisfaction with the work of nurses has a significant impact on providing better patient care as well as reducing the risk of professional burnout of nurses.